Report on two African mealybug species (Hemiptera: Sternorrhyncha: Coccomorpha) - Williams, D.j.; Matile-Ferrero, D. (Zootaxa, 2020)
Most mealybug species in the Afrotropical Region have been described or redescribed adequately and their identities are now well established. The species are listed in the catalogue of world species by Ben-Dov (1994) and in ScaleNet, an online database of the scale insects (García-Morales et al. 2019). The genera found in South Africa, and their type species, were discussed by Millar (2002). However, two species remain that have not been discussed since they were described, and their identities remain obscure. Here we discuss these species.